STRES AKADEMIK SEBAGAI PREDIKTOR KESEHATAN MENTAL PADA MAHASISWA FKM UIN SU - Fatma Indriani; Sylva Qamara Nur Fadilah (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Mental health among young people is receiving increasing attention. This study aims to determine the relationship between academic stress levels and mental health among students at the Faculty of Public Health, State Islamic University of Medan (UIN SU). The method used was a quantitative correlational survey approach. Data were obtained from 131 students at the Faculty of Public Health, State Islamic University of Medan (UIN SU), using incidental sampling. The measurement tools used were the Perceived Academic Stress Scale (PASS) and the Brief Mental Health Inventory (BMHI-12). Regression analysis was used. The results showed a negative effect of academic stress on mental health among students at the Faculty of Public Health, State Islamic University of Medan (UIN SU Medan), with an effective contribution of 19.3%. These findings demonstrate the importance of stress management strategies in higher education environments to maintain student mental well-being..Keyword: Mental Health; Collage Students; Academic Stress. Abstrak: Kesehatan mental pada generasi muda semakin mendapat perhatian. Penelitian ini bertujuan untuk mengetahui hubungan antara tingkat stres akademik dengan kesehatan mental pada mahasiswa FKM UIN SU. Metode yang digunakan adalah kuantitatif korelasional dengan pendekatan survei. Data diperoleh dari 131 orang mahasiswa FKM UIN SU yang diambil dengan teknik incidental sampling. Alat ukur yang digunakan yaitu Perceived Academic Stress Scale (PASS) dan Brief Mental Health Inventory (BMHI-12)). Teknik analisis data yang digunakan adalah uji regresi. Hasil penelitian menunjukkan terdapat pengaruh negatif dari stress akademik terhadap Kesehatan mental pada mahasiswa FKM UIN SU Medan dimana sumbangan efektif yang diberikan sebesar 19,3%. Temuan ini menunjukkan pentingnya strategi manajemen stres di lingkungan pendidikan tinggi untuk menjaga kesejahteraan mental mahasiswa.Kata kunci: Kesehatan Mental; Mahasiswa; Stres Akademik.